2013
DOI: 10.1097/mcp.0b013e32835ceee5
|View full text |Cite
|
Sign up to set email alerts
|

Search for biomarkers in chronic obstructive pulmonary disease

Abstract: Biomarker identification in COPD is still a developing field, with increasing interest in patient phenotyping probably reflecting the challenges of biomarker development in a complex disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This could for example be achieved by large scale analysis of proteins (proteomics) or metabolites (metabolomics). Such studies have shown to result in protein fingerprints, which potentially could be used to investigate the pathophysiology of COPD in more detail, stratify patients for the treatment of COPD and provide a tool to therapy response [33,34]. Despite these promising results, it is important to realize that also this type of biomarkers should properly be validated and preferably underpinned by a mechanistic understanding of the changes in these profiles, before they can be utilized reliably as markers for disease progression or assessment of treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…This could for example be achieved by large scale analysis of proteins (proteomics) or metabolites (metabolomics). Such studies have shown to result in protein fingerprints, which potentially could be used to investigate the pathophysiology of COPD in more detail, stratify patients for the treatment of COPD and provide a tool to therapy response [33,34]. Despite these promising results, it is important to realize that also this type of biomarkers should properly be validated and preferably underpinned by a mechanistic understanding of the changes in these profiles, before they can be utilized reliably as markers for disease progression or assessment of treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…As the identification of biomarkers in COPD is a developing field, a topic of active research is the utility of biomarkers in improving subphenotyping of COPD patients 24. CCL-18 is mainly expressed by monocytes/macrophages and immature dendritic cells.…”
Section: Discussionmentioning
confidence: 99%